2009
DOI: 10.1007/s10096-009-0840-3
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila monoclonal antibody subgroups and DNA sequence types isolated in Canada between 1981 and 2009: Laboratory Component of National Surveillance

Abstract: Legionella pneumophila (Lp) is a significant cause of nosocomial, community-acquired, and travel-associated pneumonia in industrialized regions. Legionellosis has been a nationally notifiable disease in Canada since 1986, with an average of 75 cases reported annually; however, only the most severe, and often fatal, cases are reported or investigated. Here, epidemiological relationships, types, and distribution of Lp referrals to the Canadian national reference center were studied. Lp strains from different yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
41
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 28 publications
11
41
4
Order By: Relevance
“…One report in South Korea showed that the mompS locus had the most alleles (2). Similarly, another study conducted in Canada obtained the same result that locus mompS provided the most alleles (22). However, one study on SBT of L. pneumophila strains in mainland China indicated that mip and flaA individually provided the most alleles in the isolates from cooling water and hot spring water (19).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…One report in South Korea showed that the mompS locus had the most alleles (2). Similarly, another study conducted in Canada obtained the same result that locus mompS provided the most alleles (22). However, one study on SBT of L. pneumophila strains in mainland China indicated that mip and flaA individually provided the most alleles in the isolates from cooling water and hot spring water (19).…”
Section: Discussionmentioning
confidence: 80%
“…Among eight complexes generated in the minimum spanning tree, only four were related to Macau STs. The subtype distribution of L. pneumophlia strains isolated from Macau was not as extensive as that from other cities (20,22,23). However, in complex I, ST1 from Macau was the major STs involved in, which reflects the concentration of local types.…”
Section: Discussionmentioning
confidence: 85%
“…A consensus trend emerged, with all data revealing both a high level of genetic diversity in Legionella and the emergence of specific groups of clones that showed high similarities and were responsible for both sporadic legionellosis cases and worldwide outbreaks (1,4,26,34,35,37,49,58). In particular, isolates from ST1 (which includes the widely distributed Paris strain), ST47, and ST222 have been detected in sporadic and outbreak cases.…”
mentioning
confidence: 92%
“…Several studies combined these different methodologies to infer the distribution of Legionella isolates, especially from L. pneumophila serogroup 1, using collections of isolates sampled all over the world-in Japan (1), Canada (49,58), the United States (35), South Korea (37), and Europe (22,23,26). A consensus trend emerged, with all data revealing both a high level of genetic diversity in Legionella and the emergence of specific groups of clones that showed high similarities and were responsible for both sporadic legionellosis cases and worldwide outbreaks (1,4,26,34,35,37,49,58).…”
mentioning
confidence: 99%
“…By using the published neuA primers (15), standard SBT could be applied in all strains belonging to SG1 and to some other SGs. However, in some non-SG1 L. pneumophila strains, the neuA gene could not be amplified (1,11,16,20). It was considered likely therefore that this was due to either the heterogeneity of neuA DNA sequence preventing primer binding or the absence of the gene in some of these non-SG1 strains, as suggested by microarray analysis (3).…”
mentioning
confidence: 99%